Outcome of Pediatric Humerus Fracture Treated With Close Reduction and Elastic Intramedullary Nailing - Yogi, Sushil; Shrestha, Dinesh Kumar; KC, Dipendra; Karki, Prateek; Shrestha, Sabin (Journal of Nepalgunj Medical College, 2021)
Introduction: Pediatric humeral shaft fractures are infrequent fractures only secondary to trauma or any of the pathological changes in the bone; representing two to 5.5% of all pediatric fractures and occurring predominantly in children younger than three years or older than 12 years of age. These fractures can usually be treated conservatively with functional bracing and splints however conditions like inability to maintain an acceptable reduction, open fractures, floating elbow, closed head injury, and polytrauma patient requiring early weight bearing warrant the surgical intervention. The intramedullary elastic nails have been found to be more effective in treating fracture shaft of humerus of pediatric age group in comparison over other implants used. Aims:The aim of this cross-sectional observational study was to evaluate the outcome of shaft of humerus fracture in children treated with retrograde intramedullary kirschner’s wire. Methods: This prospective study was conducted in the department of Orthopedics in Nepalgunj Medical College Teaching, Kohalpur from January 2020 to March 2021 in 26 children. Children were evaluated for age, sex, side of injury, mechanism of injury, time period for union, implant removal time, outcome and accompanying complications. Patients were evaluated using Broberg and Morrey scoring system for elbow functions and modified Dash criteria for shoulder function. Results: In this study of 26 children, 65.4% were boys and 34.6% were girls with average age of 9.58 ± 2.1 years. Left side was prominent side for injury with 69.2%. The average duration for union was found to be 10.04 ± 1.42 weeks. The implant was removed at 24.19 ±1.57 weeks. Based on Broberg and Morrey score system for elbow, 23 (88.46%) children had excellent result and three (11.54%) had good result. While evaluating for Disabilities of the Arm, Shoulder and Hand (DASH) score for shoulder joint evaluation; all children had excellent result. Conclusion: The treatment of pediatric humeral shaft fracture by close reduction and intramedullary kirschner’s wire is safe, easy and cost effective operative procedure with good results.